Associations between IL-23R gene polymorphisms and the susceptibility of rheumatoid arthritis: a meta-analysis - Zou, Qinghua; Zhao, Yi; Wang, Yong; Fang, Yongfei; Liu, Yi (Artificial cells, nanomedicine, and biotechnology, 2019)
This meta-analysis was aimed to verify the influences of interleukin 23 receptor (IL-23R) rs11209026 and rs2201841 polymorphisms on the susceptibility of rheumatoid arthritis (RA). We searched potentially relevant studies on the relationships of IL-23R gene rs11209026 and rs2201841 polymorphisms with RA susceptibility from PubMed (Medline), CNKI and EMBASE web databases. Crude odds ratios (ORs) along with 95% confidence intervals (95% CIs) were calculated to assess the strength of association through the fixed- or random-effects model. Eight published articles containing 5544 RA patients and 5532 health individuals were included in our meta-analysis. In total analysis, we found IL-23R gene rs11209026 polymorphism was not related to RA susceptibility in all genetic models, but there was a significant association between rs2201841 polymorphism and RA susceptibility under G vs. A model. In stratified analysis by ethnicity, an increased RA susceptibility was detected for rs2201841 polymorphism in Caucasian group. The results of meta-analysis indicated that IL-23R gene rs2201841 polymorphism might be a susceptible factor for RA under G vs. A model, especially in Caucasian population.